Numerical Simulation and Optimization of Water Hammer Protection Schemes for Long-Distance Gravity-Pressurized Water Conveyance Systems - HUANG Wei, LIAO Chen-xi, HUANG Xin, GU Ping, LIU Bin, HUANG Zi-yang (长江科学院院报)
[Objective] When the water level difference between the upstream and downstream of a long-distance gravitational water conveyance system is small, gravity flow alone cannot ensure the required design flow rate. In such cases, the intake pumping station must be activated during high-flow conveyance periods to provide pressurized supply, forming a combined gravity and pressurized flow system. The hydraulic characteristics of such systems are more complex than those of pure gravity-driven systems. Accidental pump shutdowns can easily induce water column separation in the pipeline, leading to water hammer upon rejoining that poses a significant threat to project safety. [Methods] To address this issue, this study employed the method of characteristic curve to conduct one-dimensional numerical simulations of transient hydraulic processes for four water hammer protection schemes: (1) air valve, (2) air valve + terminal valve, (3) air valve + terminal valve + overflow pipe, and (4) air valve + air valve surge chamber. [Results] In long-distance gravity-pressurized water conveyance systems where the upstream elevation was higher than that of the downstream, accidental pump shutdowns without any protective measures would generate decompression waves that caused extreme negative pressure and water column separation inside the pipeline. The subsequent compression wave reflected from the downstream outlet reservoir would cause the separated water column to rejoin, potentially resulting in pipe rupture. Therefore, effective protective measures must be adopted to eliminate extreme negative pressure in the pipeline. When using an air valve alone for water hammer protection, the minimum pressure within the pipeline was effectively increased, but the range of protection was limited. In the air valve + terminal valve scheme, the compression wave generated by the closure of the terminal valve failed to effectively mitigate the negative pressure and may even result in excessive maximum pressure due to poor closure regulation of the terminal valve. Adding an overflow pipe to this combined scheme effectively reduced the maximum pressure in the pipeline. However, since the overflow pipe reflected part of the compression wave generated by the terminal valve closure, it had an adverse effect on negative pressure protection. [Conclusions] The air valve surge chamber, combining a surge pipe and an air valve with both water and air compensation functions, is used in combination with an air valve to form a protection scheme that effectively controls both positive and negative pressures in the pipeline. This solution achieves balance between engineering safety and cost-efficiency, making it the preferred protective measure for long-distance gravity-pressurized water conveyance systems.